2020
DOI: 10.3390/w12102855
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Riparian Vegetation in Agricultural Landscapes Influences Spider Communities and Aquatic-Terrestrial Linkages

Abstract: Riparian habitats are important ecotones connecting aquatic and terrestrial ecosystems, but are often highly degraded by human activities. Riparian buffers might help support impacted riparian communities, and improve trophic connectivity. We sampled spider communities from riparian habitats in an agricultural catchment, and analyzed their polyunsaturated fatty acid (PUFA) content to quantify trophic connectivity. Specific PUFAs are exclusively produced by stream algae, and thus are used to track uptake of aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 67 publications
4
17
0
Order By: Relevance
“…10 mg/g dry mass). High EPA content in riparian spiders was also reported by other studies (Fritz et al, 2017;Ramberg et al, 2020), although our results show even higher EPA content than e.g., the 2-3 mg/g dry mass found by Ramberg et al (2020). The ω3/ ω6 ratio is often employed to distinguish autochthonous versus allochthonous food sources in aquatic food webs and to assess the relative consumption of aquatic versus terrestrial material by consumers.…”
Section: Pufa Transfersupporting
confidence: 74%
See 1 more Smart Citation
“…10 mg/g dry mass). High EPA content in riparian spiders was also reported by other studies (Fritz et al, 2017;Ramberg et al, 2020), although our results show even higher EPA content than e.g., the 2-3 mg/g dry mass found by Ramberg et al (2020). The ω3/ ω6 ratio is often employed to distinguish autochthonous versus allochthonous food sources in aquatic food webs and to assess the relative consumption of aquatic versus terrestrial material by consumers.…”
Section: Pufa Transfersupporting
confidence: 74%
“…In fact, ground spiders might specifically accumulate/retain aquatic EPA such as other organisms that have been shown to have a higher transfer efficiency for PUFAs compared to bulk carbon (Gladyshev et al, 2011). In accordance to that, the mixing model including PUFAs estimated a higher proportion of aquatic material in both spider types' diets than the model using only δ 13 C. While Ramberg et al (2020) found a significantly higher EPA content in lycosid than tetragnathid spiders, we found no significant difference in EPA content between the spider types. In contrast, SDA content (and ω3/ ω6 ratio) was higher in web spiders than ground spiders in spring, albeit only significantly at the Necker.…”
Section: Comparison Of Spider Typessupporting
confidence: 54%
“…Spiders are an excellent model group of organisms to study differences between developmental phases of stands because they are very sensitive to changes in habitat structure and microclimatic conditions (Oxbrough et al 2005;Stańska et al 2016;Lafage et al 2019;Ramberg et al 2020). Moreover, spiders are good indicators of both ecosystem disturbance resulting from forest management (Pearce & Venier 2006) and succession stages (Haase & Balkenhol 2015;Hazzi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We observed more chironomid midges at unbuffered reaches which are weak fliers and their dispersal has been shown to be restricted to the stream edges [74]. Therefore, higher abundances with active aerial dispersing taxa at the buffered reaches in our study indicate the potential for the reciprocal transfer of subsidies to terrestrial ecosystems [5,47,[75][76][77].…”
Section: Implications For Cross-ecosystem Connectivitymentioning
confidence: 47%